The Effectiveness of Using English Movies with English Subtitles in Teaching Vocabulary: A Classroom Action Research: Ismail - Ismail (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
This study aimed to determine the effectiveness of media usage movies with English subtitles in teaching vocabulary in the form of comprehension of descriptive text in grade VIII of SMPIT Al Fitrah Al Islamy Mangelewa Dompu School Year 2022/2023 Learning outcomes in this study include learning achievement in the form of cognitive skill and vocabulary mastery. This study was a Classroom Action Research study where the population is the whole class VIII SMPIT Al Fitrah Al Islamy Mangelewa Dompu School Year 2022/2023 Sampling was done by Probability sampling technique for the population in the unit class. Samples of the study were class VIII B a Main class that uses conventional teaching (lectures) and VIII A as a Comparative class that uses media movies with subtitles. The data were obtained through a pretest to know the students’ abilities. The statistical test used to test the hypothesis was the Mann-Whitney U test with a normal curve approach Z performed on the data post-test. Data post-test shows at the 0.05 significance level, the value of Z table = 1.99, and Z count (3.25)> Z table (1.99). Because the Z count is greater than the Z table, then Ha is accepted and Ho is rejected. This suggests that the using of media movies with English subtitles is effective in increasing knowledge of vocabulary in class VIII of SMPIT Al Fitrah Al Islamy Mangelewa